Successful Post-Resuscitation Care in End-Stage Renal Disease Patients: A Case Report - Merry; Made Septyana Parama Adi; I Gusti Agung Gede Utara Hartawan; I Gusti Ngurah Mahaalit Aribawa; I Putu Fajar Narakusuma; I Gusti Agung Made Wibisana Kurniajaya (Journal of Anesthesiology and Clinical Research, 2025)
Introduction: Cardiac arrest in end-stage renal disease (ESRD) patients presents unique challenges due to their complex medical conditions. Post-resuscitation care for these patients requires careful management of various factors, including hemodynamic instability, electrolyte imbalances, and fluid overload. This case report describes the successful post-resuscitation care of an ESRD patient who experienced cardiac arrest and achieved a return of spontaneous circulation (ROSC). Case presentation: A 50-year-old female with ESRD on hemodialysis (HD) presented with acute dyspnea and cardiac arrest. After 8 minutes of cardiopulmonary resuscitation (CPR), ROSC was achieved. The patient was managed with a comprehensive post-resuscitation care protocol, including brain resuscitation (targeted temperature management, ventilation optimization, and hemodynamic control) and sustained low-efficiency dialysis for fluid balance. Despite the severity of her condition, the patient showed significant neurological recovery and was successfully extubated after 7 days of mechanical ventilation. She was discharged after 12 days with follow-up for her chronic conditions. Conclusion: This case highlights the importance of individualized management strategies for ESRD patients post-cardiac arrest, including the need for prolonged resuscitation and careful monitoring to improve patient outcomes.